Polymer Distribution and Mechanism Conversion in Multiple Media of Phase-Separated Controlled-Release Film-Coating - Lu Chen; Guobao Yang; Xiaoyang Chu; Chunhong Gao; Yuli Wang; Wei Gong; Zhiping Li; Yang Yang; Meiyan Yang; Chunsheng Gao (MDPI AG, 2019)
Phase-separated films of water-insoluble ethyl cellulose (EC) and water-soluble hydroxypropyl cellulose (HPC) can be utilized to tailor drug release from coated pellets. In the present study, the effects of HPC levels and the pH, type, ionic strength and osmolarity of the media on the release profiles of soluble metoprolol succinates from the EC/HPC-coated pellets were investigated, and the differences in drug-release kinetics in multiple media were further elucidated through the HPC leaching and swelling kinetics of the pellets, morphology (SEM) and water uptake of the free films and the interaction between the coating polymers and the media compositions. Interestingly, the drug release rate from the pellets in different media was not in agreement with the drug solubility which have a positive correlation with the drug dissolution rate based on Noyes⁻Whitney equation law. In particular, the drug release rate in acetate buffer at pH 4.5 was faster than that in other media despite the solubility of drug was relatively lower, regardless of the HPC levels. It may be attributed to the mutual effect between the EC and acetate buffer, which improved the permeability of the film. In contrast, the release of drug in HCl solution was dependent on the HPC levels. Increasing the levels of HPC increased the effects of hydrogen ions on the polymer of HPC, which resulted in a lower viscosity and strength of the gel, forming the larger size of pores in polymer films, thus increasing the drug diffused from the coating film. Further findings in phosphate buffer showed a reduction in the drug release compared to that in other media, which was only sensitive to the osmolarity rather than the HPC level and pH of the buffer. Additionally, a mathematical theory was used to better explain and understand the experimentally measured different drug release patterns. In summary, the study revealed that the effects of the media overcompensated that of the drug solubility to some extent for controlled-release of the coating polymers, and the drug release mechanism in multiple media depend on EC and HPC rather than on HPC alone, which may have a potential to facilitate the optimization of ideally film-coated formulations.